Penerapan Prinsip-Prinsip Good Governance (Studi Kasus dalam Proses Pengangkatan Pejabat Struktural Eselon II di Lingkungan Pemerintah Kota Bandar Lampung) - Andre Pebrian Perdana (Inovasi Pembangunan : Jurnal Kelitbangan, 2017)
Appointment of civil servants in the structural positions should comply to the principles of good governance, but in practice it was still dominated by various political interests, kinship and the intervention of any outside organization system of the Government. The formulation of the problem of the research was: "How was the implementation of good governance principles on Structural Echelon II Appointment Process in the City of Bandar Lampung Government?” The purpose of the research was to analyze the implementation of good governance principles on the structural echelon II appointment process in the City of Bandar Lampung Government. The study employed a qualitative research. Data was collected through interview and documentation. Data were then analyzed qualitatively following the stages consisting data reduction, data display and conclusion. The results of this study indicated that the implementation of good governance principles in the process of appointment of structural echelon II officials in the City of Bandar Lampung Environment was not been optimally applied. The process was not a transparent appointment because the nomination process from regional work units, personal proposal or suggestion from Tim Baperjakat until the signing of the Decree was kept secretive not distributed to the involved parties or the media. Appointment process of echelon II officials did not comply with the regulations of employment in effect or was not based on the supremacy of the laws. The principles of participation were still not optimally observed because the participation of the community was still in queu due to the fact that there was not any internal mechanism confidential to make the public awared of any specific appointments.